Curricular Issue under the Federal Context of Nepal - Sharma Gyawali, Bishnu (Ganeshman Darpan, 2022)
Nepal has become a federal country after the promulgation of a new constitution in 2015. In this context, this study concerns a very new issue in the federal Nepalese education system. The purpose of this study is to find out the curricular issues in the federal system of Nepal. In this study, I explored power allocation issues, quality ensuring issues, standard maintenance issues ICT related issues, and employment issues in the area of the curriculum. Curriculum experts should consider these issues while developing the federal system of the curriculum in Nepal.